Thermodynamic analysis of high pressure hydrogen gas refueling system with turbo-expanders - Jun YOSHIDA (The Japan Society of Mechanical Engineers, 2019)
This paper introduces a new hydrogen refueling system with a micro-scale hydrogen turbo-expander that enables us to replace a conventional low temperature refrigerator. From the process simulation of hydrogen refueling to the tank of a typical Fuel Cell Vehicle (FCV), the system is thermodynamically verified to be capable of refueling 5 kg-H2 within 3 minutes by the direct expansion in the micro-scale hydrogen turbo-expander. For the realization of this new concept, a process design approach of a high pressure hydrogen refueling system with the micro-scale hydrogen turbo-expander is described. In this process design, a turbine-compressor type is adopted to the micro-scale hydrogen turbo-expander unit, and an extracted power from the turbine side is consumed as a compressor power which is equipped on the opposite side of the turbine rotor. As a consequence of the thermodynamic analysis and simulation for the proposed system including the turbo-expander with adiabatic efficiency around65 %, it reveals that the new system provides some significant advantages compared with the conventional process. From a feasible investigation of this system, several advantageous features such as 1) high energy conservation, 2) compactness, 3) initial cost and operation cost, and, 4) system expandability (modification for shorter time refueling) are also described when it is compared with the existing system.